Analysis Of Budget Preparation Methods In The Population And Civil Registration Service Of Nias Regency - Zai, Kurniawan Sarototonafo; Hulu, Tri Hartati Sukartini; Waruwu, Noviza Asni; Bu'ulolo, Nanny Artatina (Universitas Dehasen Bengkulu, 2025)
Recognizing the importance of the budget in determining the activities to be implemented within the agency, it is crucial to prepare a detailed budget to avoid underfunding or overspending in carrying out these activities. With a budget, each function within the agency, particularly the Nias Regency Population and Civil Registration Office, has the necessary work services to carry out activities as outlined in the budget for a specific period. The purpose of this study is to determine the budget preparation process implemented by the Nias Regency Population and Civil Registration Office. The title of this study is